In-vitro cytotoxicity activity of potato (Solanum tuberosum. L) peel extracts against human gingival fibroblasts - Khong Mei Xuan; Anne Handrini Dewi; Ivan Arie Wahyudi (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Potato peel is often regarded as waste although it contains phenolic compounds, glycoalkaloids, and flavonoid. This study aimed to evaluate the effect of different concentrations of potato peel extracts on the viability of Human Gingival Fibroblasts (HGF). Potato peel extracts were prepared by a maceration technique. The 96-well tissue culture micro titre plates were seeded with HGF at a density of 2×104 cells/100 μL and incubated for 24 hours. Next, 100 μL of potato peel extracts at a concentration of 62.5 μg/mL, 125 μg/mL, 250 μg/mL, 500 μg/mL, and 1000 μg/mL and a medium (control) were dispensed into the well of the cell culture. Each concentration was evaluated for its viability with 3 replicate samples. The results of the MTT test were analyzed statistically using one-way ANOVA and LSD test. The mean and standard deviation of the viable HGF after incubated with the potato peel extract at the concentration of 62.5 μg/mL, 125 μg/mL, 250 μg/mL, 500 μg/mL, and 1000 μg/mL were 98.67% ± 3.56, 88.34% ± 0.79, 55.42% ± 3.96, 28.33% ± 0.60, and 26.26% ± 0.53, respectively. The percentage of non-viable HGF increased with an increase in the concentration of the potato peel extract. The ANOVA test result showed a significant influence of various concentrations of the potato peel extract on the viability of HGF (p<0.05). The result of the LSD-test showed a significant difference among all the treatment groups (p<0.05). A higher concentration of potato peel extracts increased the viability of HGF cell line and the concentrations of 62.5 μg/mL and 125 μg/mL were considered non-cytotoxic.